Perancangan Buku Cerita Bergambar Mengenai Cryptozoology Indonesia - Ferrari, Rifaldi Feliandra; Ekawardhani, Yully Ambarsih (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2023)
Cryptozoolology is a study of animals whose existence is still questioned or debated. This animal is part of folklore, mythology, animals that have become extinct and are still found today animals or creatures whose existence is still mysterious is called cryptids and people who are experts or examine cryptids are called cryptozoolologists. In Indonesia there are Cryptids which are famous for the world and even some of these animals are famous for Western explorers. So that this information is stored in a limited manner, even though these creatures are naturally in Indonesia. Therefore we need information media about cryptids from Indonesia. To get their own data from books, previous research, and the internet as well as for community observation through interviews. To solve this problem, an information medium was created that explained about cryptids in Indonesia, namely an encyclopedia illustration book.